Standards of care for obsessive–compulsive disorder centres - Menchón, José M. (Int J Psychiatry Clin Pract, 2016)
In recent years, many assessment and care units for obsessive–compulsive disorder (OCD) have been set up in order to detect, diagnose and to properly manage this complex disorder, but there is no consensus regarding the key functions that these units should perform. The International College of Obsessive-Compulsive Spectrum Disorders (ICOCS) together with the Obsessive Compulsive and Related Disorders Network (OCRN) of the European College of Neuropsychopharmacology (ECNP) and the Anxiety and Obsessive Compulsive Disorders Section of the World Psychiaric Association (WPA) has developed a standards of care programme for OCD centres. The goals of this collaborative initiative are promoting basic standards, improving the quality of clinical care and enhance the validity and reliability of research results provided by different facilities and countries.